Philosophy and the constitution of the intercultural sense - Komel, Dean (Primerjalna književnost, 2004)
The author discusses the idea of a constitution of intercultural behaviour from a phenomenological and hermeneutical point of view. In his opinion, the historical tradition of philosophical thought has already developed intercultural elements. The question arises as to whether interculturality is only one aspect of the contemporary cynical annihilation of the word or, on the contrary, if it offers a different comprehension of human existence, a way to escape from nihilism. The author's reply stresses the possibility of a hermeneutical constitution of intercultural sense, connected with a possible future European dialogue as a way of mutual understanding within one culture and among different cultures.
Keywords: filozofija kulture; kulturna identiteta; interkulturalnost; hermenevtika; nihilizem